2011
DOI: 10.1001/archdermatol.2011.140
|View full text |Cite
|
Sign up to set email alerts
|

Cutaneous Melanoma and Other Skin Cancer Screening Among Hispanics in the United States: A Review of the Evidence, Disparities, and Need for Expanding the Intervention and Research Agendas

Abstract: S kin pigmentation and sun sensitivity vary widely among US Hispanics, 1 whose median number of nevi (the strongest melanoma risk factor) is somewhat lower than in whites yet higher than in Asians or blacks. 2 The correlation between number of nevi and age is stronger in Hispanics and non-Hispanic whites than in other ethnoracial groups. 2 Among Hispanics, acculturation to the United States might lead to decreased sun safety practices. 3 Nationwide data from 1992 through 2007 reveal that melanoma incidence amo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 15 publications
0
15
1
Order By: Relevance
“…23 Other studies have indicated that Hispanics are under-screened for skin cancer compared to other ethnic groups despite the increasing incidence of melanoma in this population. 24,25 To our knowledge, our study is the first that has analyzed the incidence of anorectal melanoma in Hispanic whites and non-Hispanic whites. Although this may suggest a role for improved screening among those with Hispanic ethnicity, additional studies must be done to corroborate these results and further elucidate the association of Hispanic ethnicity with anorectal melanoma.…”
Section: Discussionmentioning
confidence: 99%
“…23 Other studies have indicated that Hispanics are under-screened for skin cancer compared to other ethnic groups despite the increasing incidence of melanoma in this population. 24,25 To our knowledge, our study is the first that has analyzed the incidence of anorectal melanoma in Hispanic whites and non-Hispanic whites. Although this may suggest a role for improved screening among those with Hispanic ethnicity, additional studies must be done to corroborate these results and further elucidate the association of Hispanic ethnicity with anorectal melanoma.…”
Section: Discussionmentioning
confidence: 99%
“…Enhancing primary prevention strategies, such as targeted education, may be important during this period of uncertainty on screening guidelines (Andreeva and Cockburn, 2011). …”
Section: Discussionmentioning
confidence: 99%
“…Sun protection can reduce the risk of skin cancer [2]. However, use of sun protection is low among Hispanics, and Hispanics have less knowledge of skin cancer risk factors and lower perceived risk of getting skin cancer compared to NHWs [21,22,13,23]. …”
Section: Introductionmentioning
confidence: 99%